2017
DOI: 10.1177/1010428317711033
|View full text |Cite
|
Sign up to set email alerts
|

Apatinib for metastatic breast cancer in non-clinical trial setting: Satisfying efficacy regardless of previous anti-angiogenic treatment

Abstract: Apatinib is a novel tyrosine kinase inhibitor targeting vascular endothelial growth factor receptor 2. This study aimed to evaluate the efficacy and safety of apatinib in metastatic breast cancer (MBC) under non-clinical trial setting, and to study the impact of previous antiangiogenic treatment to the efficacy of apatinib. 52 MBC patients treated with apatinib under non-clinical trial setting in Fudan University Shanghai Cancer Center between January 1st 2015 and October 1st 2016 were included. All patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 32 publications
4
11
0
Order By: Relevance
“…In our study, most cases of hypertension, proteinuria, and hand-foot syndrome were of grades 1 and 2, with incidences of 56.86%, 49.02%, and 52.94%, respectively. These findings were generally consistent with the results of previous studies on other solid cancers [26,27]. It is worth noting that one patient showed severe hemorrhinia, possibly related to the treatment, which could indicate that VEGFR inhibitor drugs may increase bleeding risk in patients.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, most cases of hypertension, proteinuria, and hand-foot syndrome were of grades 1 and 2, with incidences of 56.86%, 49.02%, and 52.94%, respectively. These findings were generally consistent with the results of previous studies on other solid cancers [26,27]. It is worth noting that one patient showed severe hemorrhinia, possibly related to the treatment, which could indicate that VEGFR inhibitor drugs may increase bleeding risk in patients.…”
Section: Discussionsupporting
confidence: 91%
“…The AEs observed in our study were either similar to those reported in previous studies of apatinib [10][11][12]19,20,[32][33][34][35] or to those of other VEGFR inhibitors 24,36,37 . Most grade 3 or 4 AEs were hypertension, proteinuria, HFS, thrombocytopenia, and mucositis oral, which was expected and tolerable for this patient population.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, it was found that preceding therapy with bevacizumab had no effect on the efficacy of apatinib. 45 …”
Section: The Clinical Research Regarding Apatinibmentioning
confidence: 99%